2022
DOI: 10.1186/s13756-022-01194-9
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater-based surveillance in Italy leading to the first detection of mcr-10-positive Klebsiella quasipneumoniae

Abstract: Wastewater-based surveillance enabled the first detection of the mobile colistin resistance gene mcr-10 in Italy. This plasmid-borne resistance gene was found in strains of Klebsiella quasipneumoniae isolated from samples of human raw sewage collected over several months. Although the isolates were phenotypically susceptible to colistin, the emergence of mcr-10 is concerning due to the highly variable expression of the gene and the potential for horizontal transfer to other species. In addition, the strains al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
6
2
Order By: Relevance
“…Most mcr-10-harbouring isolates reported in previous studies were susceptible to colistin [17][18][19][20], but we demonstrated that mcr-10-harbouring K. pneumoniae showed decreased susceptibility to colistin in BHIB. mcr-9 expression in colistin-resistant Enterobacterales was regulated by the two-component system QseBC [15], but colistin-resistant Enterobacterales harbouring mcr-10 had no two-component system like QseBC.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Most mcr-10-harbouring isolates reported in previous studies were susceptible to colistin [17][18][19][20], but we demonstrated that mcr-10-harbouring K. pneumoniae showed decreased susceptibility to colistin in BHIB. mcr-9 expression in colistin-resistant Enterobacterales was regulated by the two-component system QseBC [15], but colistin-resistant Enterobacterales harbouring mcr-10 had no two-component system like QseBC.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus far, mcr-10-harbouring isolates have been detected in Cronobacter sakazakii, Enterobacter spp., E. coli and Klebsiella spp. from humans, the environment, companion animals and livestock in several countries, including Australia, Canada, PR China, Egypt, Italy, Japan, the Netherlands, Sierra Leone, Switzerland, the UK and Vietnam [17][18][19][20]. These mcr-10-harbouring isolates possessed no carbapenemase-encoding gene.…”
Section: Discussionmentioning
confidence: 99%
“…Two multiplex PCRs were set up using the QIAGEN Multiplex PCR Plus Kit for mcr genes from 1 to 5 and from 6 to 10 [ 50 ]. For the first nine mcr, we used primers described in [ 50 , 51 ], while for mcr -10 primers design was based on the first submitted gene sequence [ 52 ], as described in [ 16 ]. PCR reactions were composed as follows: mcr 1–5 genes: 6.75 µL of RNase-free water, 12.5 µL of Multiplex PCR master mix (2×), 2.5 µL of Coral Dye and 1.25 µL of primer mix 10× (0.2 µL of each primer) mcr 6–10 genes: 6.75 µL of RNase-free water, 12.5 µL of Multiplex PCR master mix (2×), 2.5 µL of Coral Dye and 1.25 µL of primer mix 10× (0.2 µL of each primer).…”
Section: Methodsmentioning
confidence: 99%
“…We performed both short-read (on Miniseq, Illumina, San Diego, CA, USA) and long-read sequencing (on MinION, Oxford Nanopore Technologies, Oxford, UK). Genomic DNA extraction, Illumina libraries and sequencing runs on the MiniSeq platform were performed as previously described [ 16 ]. The DNA library for MinION was prepared using the Rapid Barcoding kit (SQK-RBK004) following the manufacturer’s instructions ( , accessed on 2 March 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation